--- a/src/HOL/Deriv.thy Tue Jan 13 06:55:13 2009 -0800
+++ b/src/HOL/Deriv.thy Tue Jan 13 06:57:08 2009 -0800
@@ -9,7 +9,7 @@
header{* Differentiation *}
theory Deriv
-imports Lim Univ_Poly
+imports Lim Polynomial
begin
text{*Standard Definitions*}
@@ -1412,34 +1412,71 @@
lemma lemma_DERIV_subst: "[| DERIV f x :> D; D = E |] ==> DERIV f x :> E"
by auto
+
subsection {* Derivatives of univariate polynomials *}
-
-
-primrec pderiv_aux :: "nat => real list => real list" where
- pderiv_aux_Nil: "pderiv_aux n [] = []"
-| pderiv_aux_Cons: "pderiv_aux n (h#t) =
- (real n * h)#(pderiv_aux (Suc n) t)"
-
definition
- pderiv :: "real list => real list" where
- "pderiv p = (if p = [] then [] else pderiv_aux 1 (tl p))"
+ pderiv :: "'a::real_normed_field poly \<Rightarrow> 'a poly" where
+ "pderiv = poly_rec 0 (\<lambda>a p p'. p + pCons 0 p')"
+
+lemma pderiv_0 [simp]: "pderiv 0 = 0"
+ unfolding pderiv_def by (simp add: poly_rec_0)
+lemma pderiv_pCons: "pderiv (pCons a p) = p + pCons 0 (pderiv p)"
+ unfolding pderiv_def by (simp add: poly_rec_pCons)
+
+lemma coeff_pderiv: "coeff (pderiv p) n = of_nat (Suc n) * coeff p (Suc n)"
+ apply (induct p arbitrary: n, simp)
+ apply (simp add: pderiv_pCons coeff_pCons ring_simps split: nat.split)
+ done
-text{*The derivative*}
+lemma pderiv_eq_0_iff: "pderiv p = 0 \<longleftrightarrow> degree p = 0"
+ apply (rule iffI)
+ apply (cases p, simp)
+ apply (simp add: expand_poly_eq coeff_pderiv del: of_nat_Suc)
+ apply (simp add: expand_poly_eq coeff_pderiv coeff_eq_0)
+ done
-lemma pderiv_Nil: "pderiv [] = []"
+lemma degree_pderiv: "degree (pderiv p) = degree p - 1"
+ apply (rule order_antisym [OF degree_le])
+ apply (simp add: coeff_pderiv coeff_eq_0)
+ apply (cases "degree p", simp)
+ apply (rule le_degree)
+ apply (simp add: coeff_pderiv del: of_nat_Suc)
+ apply (rule subst, assumption)
+ apply (rule leading_coeff_neq_0, clarsimp)
+ done
-apply (simp add: pderiv_def)
-done
-declare pderiv_Nil [simp]
+lemma pderiv_singleton [simp]: "pderiv [:a:] = 0"
+by (simp add: pderiv_pCons)
+
+lemma pderiv_add: "pderiv (p + q) = pderiv p + pderiv q"
+by (rule poly_ext, simp add: coeff_pderiv ring_simps)
+
+lemma pderiv_minus: "pderiv (- p) = - pderiv p"
+by (rule poly_ext, simp add: coeff_pderiv)
+
+lemma pderiv_diff: "pderiv (p - q) = pderiv p - pderiv q"
+by (rule poly_ext, simp add: coeff_pderiv ring_simps)
+
+lemma pderiv_smult: "pderiv (smult a p) = smult a (pderiv p)"
+by (rule poly_ext, simp add: coeff_pderiv ring_simps)
-lemma pderiv_singleton: "pderiv [c] = []"
-by (simp add: pderiv_def)
-declare pderiv_singleton [simp]
+lemma pderiv_mult: "pderiv (p * q) = p * pderiv q + q * pderiv p"
+apply (induct p)
+apply simp
+apply (simp add: pderiv_add pderiv_smult pderiv_pCons ring_simps)
+done
-lemma pderiv_Cons: "pderiv (h#t) = pderiv_aux 1 t"
-by (simp add: pderiv_def)
+lemma pderiv_power_Suc:
+ "pderiv (p ^ Suc n) = smult (of_nat (Suc n)) (p ^ n) * pderiv p"
+apply (induct n)
+apply simp
+apply (subst power_Suc)
+apply (subst pderiv_mult)
+apply (erule ssubst)
+apply (simp add: mult_smult_right mult_smult_left smult_add_left ring_simps)
+done
lemma DERIV_cmult2: "DERIV f x :> D ==> DERIV (%x. (f x) * c :: real) x :> D * c"
by (simp add: DERIV_cmult mult_commute [of _ c])
@@ -1448,33 +1485,18 @@
by (rule lemma_DERIV_subst, rule DERIV_pow, simp)
declare DERIV_pow2 [simp] DERIV_pow [simp]
-lemma lemma_DERIV_poly1: "\<forall>n. DERIV (%x. (x ^ (Suc n) * poly p x)) x :>
- x ^ n * poly (pderiv_aux (Suc n) p) x "
-apply (induct "p")
-apply (auto intro!: DERIV_add DERIV_cmult2
- simp add: pderiv_def right_distrib real_mult_assoc [symmetric]
- simp del: realpow_Suc)
-apply (subst mult_commute)
-apply (simp del: realpow_Suc)
-apply (simp add: mult_commute realpow_Suc [symmetric] del: realpow_Suc)
-done
-
-lemma lemma_DERIV_poly: "DERIV (%x. (x ^ (Suc n) * poly p x)) x :>
- x ^ n * poly (pderiv_aux (Suc n) p) x "
-by (simp add: lemma_DERIV_poly1 del: realpow_Suc)
-
-lemma DERIV_add_const: "DERIV f x :> D ==> DERIV (%x. a + f x :: real) x :> D"
+lemma DERIV_add_const: "DERIV f x :> D ==> DERIV (%x. a + f x :: 'a::real_normed_field) x :> D"
by (rule lemma_DERIV_subst, rule DERIV_add, auto)
lemma poly_DERIV[simp]: "DERIV (%x. poly p x) x :> poly (pderiv p) x"
-apply (induct "p")
-apply (auto simp add: pderiv_Cons)
-apply (rule DERIV_add_const)
+apply (induct p)
+apply simp
+apply (simp add: pderiv_pCons)
apply (rule lemma_DERIV_subst)
-apply (rule lemma_DERIV_poly [where n=0, simplified], simp)
+apply (rule DERIV_add DERIV_mult DERIV_const DERIV_ident | assumption)+
+apply simp
done
-
text{* Consequences of the derivative theorem above*}
lemma poly_differentiable[simp]: "(%x. poly p x) differentiable (x::real)"
@@ -1493,11 +1515,9 @@
lemma poly_IVT_neg: "[| (a::real) < b; 0 < poly p a; poly p b < 0 |]
==> \<exists>x. a < x & x < b & (poly p x = 0)"
-apply (insert poly_IVT_pos [where p = "-- p" ])
-apply (simp add: poly_minus neg_less_0_iff_less)
-done
+by (insert poly_IVT_pos [where p = "- p" ]) simp
-lemma poly_MVT: "a < b ==>
+lemma poly_MVT: "(a::real) < b ==>
\<exists>x. a < x & x < b & (poly p b - poly p a = (b - a) * poly (pderiv p) x)"
apply (drule_tac f = "poly p" in MVT, auto)
apply (rule_tac x = z in exI)
@@ -1506,136 +1526,7 @@
text{*Lemmas for Derivatives*}
-lemma lemma_poly_pderiv_aux_add: "\<forall>p2 n. poly (pderiv_aux n (p1 +++ p2)) x =
- poly (pderiv_aux n p1 +++ pderiv_aux n p2) x"
-apply (induct "p1", simp, clarify)
-apply (case_tac "p2")
-apply (auto simp add: right_distrib)
-done
-
-lemma poly_pderiv_aux_add: "poly (pderiv_aux n (p1 +++ p2)) x =
- poly (pderiv_aux n p1 +++ pderiv_aux n p2) x"
-apply (simp add: lemma_poly_pderiv_aux_add)
-done
-
-lemma lemma_poly_pderiv_aux_cmult: "\<forall>n. poly (pderiv_aux n (c %* p)) x = poly (c %* pderiv_aux n p) x"
-apply (induct "p")
-apply (auto simp add: poly_cmult mult_ac)
-done
-
-lemma poly_pderiv_aux_cmult: "poly (pderiv_aux n (c %* p)) x = poly (c %* pderiv_aux n p) x"
-by (simp add: lemma_poly_pderiv_aux_cmult)
-
-lemma poly_pderiv_aux_minus:
- "poly (pderiv_aux n (-- p)) x = poly (-- pderiv_aux n p) x"
-apply (simp add: poly_minus_def poly_pderiv_aux_cmult)
-done
-
-lemma lemma_poly_pderiv_aux_mult1: "\<forall>n. poly (pderiv_aux (Suc n) p) x = poly ((pderiv_aux n p) +++ p) x"
-apply (induct "p")
-apply (auto simp add: real_of_nat_Suc left_distrib)
-done
-
-lemma lemma_poly_pderiv_aux_mult: "poly (pderiv_aux (Suc n) p) x = poly ((pderiv_aux n p) +++ p) x"
-by (simp add: lemma_poly_pderiv_aux_mult1)
-
-lemma lemma_poly_pderiv_add: "\<forall>q. poly (pderiv (p +++ q)) x = poly (pderiv p +++ pderiv q) x"
-apply (induct "p", simp, clarify)
-apply (case_tac "q")
-apply (auto simp add: poly_pderiv_aux_add poly_add pderiv_def)
-done
-
-lemma poly_pderiv_add: "poly (pderiv (p +++ q)) x = poly (pderiv p +++ pderiv q) x"
-by (simp add: lemma_poly_pderiv_add)
-
-lemma poly_pderiv_cmult: "poly (pderiv (c %* p)) x = poly (c %* (pderiv p)) x"
-apply (induct "p")
-apply (auto simp add: poly_pderiv_aux_cmult poly_cmult pderiv_def)
-done
-
-lemma poly_pderiv_minus: "poly (pderiv (--p)) x = poly (--(pderiv p)) x"
-by (simp add: poly_minus_def poly_pderiv_cmult)
-
-lemma lemma_poly_mult_pderiv:
- "poly (pderiv (h#t)) x = poly ((0 # (pderiv t)) +++ t) x"
-apply (simp add: pderiv_def)
-apply (induct "t")
-apply (auto simp add: poly_add lemma_poly_pderiv_aux_mult)
-done
-
-lemma poly_pderiv_mult: "\<forall>q. poly (pderiv (p *** q)) x =
- poly (p *** (pderiv q) +++ q *** (pderiv p)) x"
-apply (induct "p")
-apply (auto simp add: poly_add poly_cmult poly_pderiv_cmult poly_pderiv_add poly_mult)
-apply (rule lemma_poly_mult_pderiv [THEN ssubst])
-apply (rule lemma_poly_mult_pderiv [THEN ssubst])
-apply (rule poly_add [THEN ssubst])
-apply (rule poly_add [THEN ssubst])
-apply (simp (no_asm_simp) add: poly_mult right_distrib add_ac mult_ac)
-done
-
-lemma poly_pderiv_exp: "poly (pderiv (p %^ (Suc n))) x =
- poly ((real (Suc n)) %* (p %^ n) *** pderiv p) x"
-apply (induct "n")
-apply (auto simp add: poly_add poly_pderiv_cmult poly_cmult poly_pderiv_mult
- real_of_nat_zero poly_mult real_of_nat_Suc
- right_distrib left_distrib mult_ac)
-done
-
-lemma poly_pderiv_exp_prime: "poly (pderiv ([-a, 1] %^ (Suc n))) x =
- poly (real (Suc n) %* ([-a, 1] %^ n)) x"
-apply (simp add: poly_pderiv_exp poly_mult del: pexp_Suc)
-apply (simp add: poly_cmult pderiv_def)
-done
-
-
-lemma real_mult_zero_disj_iff[simp]: "(x * y = 0) = (x = (0::real) | y = 0)"
-by simp
-
-lemma pderiv_aux_iszero [rule_format, simp]:
- "\<forall>n. list_all (%c. c = 0) (pderiv_aux (Suc n) p) = list_all (%c. c = 0) p"
-by (induct "p", auto)
-
-lemma pderiv_aux_iszero_num: "(number_of n :: nat) \<noteq> 0
- ==> (list_all (%c. c = 0) (pderiv_aux (number_of n) p) =
- list_all (%c. c = 0) p)"
-unfolding neq0_conv
-apply (rule_tac n1 = "number_of n" and m1 = 0 in less_imp_Suc_add [THEN exE], force)
-apply (rule_tac n1 = "0 + x" in pderiv_aux_iszero [THEN subst])
-apply (simp (no_asm_simp) del: pderiv_aux_iszero)
-done
-
-instance real:: idom_char_0
-apply (intro_classes)
-done
-
-instance real:: recpower_idom_char_0
-apply (intro_classes)
-done
-
-lemma pderiv_iszero [rule_format]:
- "poly (pderiv p) = poly [] --> (\<exists>h. poly p = poly [h])"
-apply (simp add: poly_zero)
-apply (induct "p", force)
-apply (simp add: pderiv_Cons pderiv_aux_iszero_num del: poly_Cons)
-apply (auto simp add: poly_zero [symmetric])
-done
-
-lemma pderiv_zero_obj: "poly p = poly [] --> (poly (pderiv p) = poly [])"
-apply (simp add: poly_zero)
-apply (induct "p", force)
-apply (simp add: pderiv_Cons pderiv_aux_iszero_num del: poly_Cons)
-done
-
-lemma pderiv_zero: "poly p = poly [] ==> (poly (pderiv p) = poly [])"
-by (blast elim: pderiv_zero_obj [THEN impE])
-declare pderiv_zero [simp]
-
-lemma poly_pderiv_welldef: "poly p = poly q ==> (poly (pderiv p) = poly (pderiv q))"
-apply (cut_tac p = "p +++ --q" in pderiv_zero_obj)
-apply (simp add: fun_eq poly_add poly_minus poly_pderiv_add poly_pderiv_minus del: pderiv_zero)
-done
-
+(* FIXME
lemma lemma_order_pderiv [rule_format]:
"\<forall>p q a. 0 < n &
poly (pderiv p) \<noteq> poly [] &
@@ -1756,7 +1647,7 @@
apply (simp (no_asm) add: rsquarefree_def order_root del: pmult_Cons)
apply (simp add: poly_entire del: pmult_Cons)
done
-
+*)
subsection {* Theorems about Limits *}
--- a/src/HOL/Fundamental_Theorem_Algebra.thy Tue Jan 13 06:55:13 2009 -0800
+++ b/src/HOL/Fundamental_Theorem_Algebra.thy Tue Jan 13 06:57:08 2009 -0800
@@ -6,9 +6,6 @@
imports Polynomial Dense_Linear_Order Complex
begin
-hide (open) const Univ_Poly.poly
-hide (open) const Univ_Poly.degree
-
subsection {* Square root of complex numbers *}
definition csqrt :: "complex \<Rightarrow> complex" where
"csqrt z = (if Im z = 0 then
@@ -827,7 +824,7 @@
by simp
let ?r = "smult (inverse ?a0) q"
have lgqr: "plength q = plength ?r"
- using a00 unfolding plength_def Polynomial.degree_def
+ using a00 unfolding plength_def degree_def
by (simp add: expand_poly_eq)
{assume h: "\<And>x y. poly ?r x = poly ?r y"
{fix x y
@@ -1064,7 +1061,7 @@
fixes p :: "'a::{idom,ring_char_0} poly"
shows "poly p = poly 0 \<longleftrightarrow> p = 0"
apply (cases "p = 0", simp_all)
-apply (drule Polynomial.poly_roots_finite)
+apply (drule poly_roots_finite)
apply (auto simp add: UNIV_char_0_infinite)
done
@@ -1147,7 +1144,7 @@
have "s dvd (r ^ (degree s))" by blast
then obtain u where u: "r ^ (degree s) = s * u" ..
hence u': "\<And>x. poly s x * poly u x = poly r x ^ degree s"
- by (simp only: Polynomial.poly_mult[symmetric] poly_power[symmetric])
+ by (simp only: poly_mult[symmetric] poly_power[symmetric])
let ?w = "(u * ([:-a,1:] ^ (n - ?op))) * (r ^ (n - degree s))"
from oop[of a] dsn have "q ^ n = p * ?w"
apply -
@@ -1207,7 +1204,7 @@
then obtain u where u: "q ^ (Suc n) = p * u" ..
{fix x assume h: "poly p x = 0" "poly q x \<noteq> 0"
hence "poly (q ^ (Suc n)) x \<noteq> 0" by simp
- hence False using u h(1) by (simp only: poly_mult poly_exp) simp}}
+ hence False using u h(1) by (simp only: poly_mult) simp}}
with n nullstellensatz_lemma[of p q "degree p"] dp
have ?thesis by auto}
ultimately have ?thesis by blast}
@@ -1258,7 +1255,6 @@
lemma resolve_eq_raw: "poly 0 x \<equiv> 0" "poly [:c:] x \<equiv> (c::complex)" by auto
lemma resolve_eq_then: "(P \<Longrightarrow> (Q \<equiv> Q1)) \<Longrightarrow> (\<not>P \<Longrightarrow> (Q \<equiv> Q2))
\<Longrightarrow> Q \<equiv> P \<and> Q1 \<or> \<not>P\<and> Q2" apply (atomize (full)) by blast
-lemma expand_ex_beta_conv: "list_ex P [c] \<equiv> P c" by simp
lemma poly_divides_pad_rule:
fixes p q :: "complex poly"
@@ -1382,8 +1378,6 @@
lemma elim_neg_conv: "- z \<equiv> (-1) * (z::complex)" by simp
lemma eqT_intr: "PROP P \<Longrightarrow> (True \<Longrightarrow> PROP P )" "PROP P \<Longrightarrow> True" by blast+
lemma negate_negate_rule: "Trueprop P \<equiv> \<not> P \<equiv> False" by (atomize (full), auto)
-lemma last_simps: "last [x] = x" "last (x#y#ys) = last (y#ys)" by simp_all
-lemma length_simps: "length [] = 0" "length (x#y#xs) = length xs + 2" "length [x] = 1" by simp_all
lemma complex_entire: "(z::complex) \<noteq> 0 \<and> w \<noteq> 0 \<equiv> z*w \<noteq> 0" by simp
lemma resolve_eq_ne: "(P \<equiv> True) \<equiv> (\<not>P \<equiv> False)" "(P \<equiv> False) \<equiv> (\<not>P \<equiv> True)"